Analisis Tingkat Kesehatan Koperasi pada Koperasi Simpan Pinjam di Kabupaten Tulang Bawang Barat - Herry Goenawan Soedarsa; Desty Natalia (Universitas Bandar Lampung (UBL), 2016)
The purpose of this study was to determine determine and advise the Credit Unions in Tulang Bawang Barat about the soundness of the cooperative to assess, the soundness of the cooperative visits from capital, asset quality, management, efficiency, liquidity, independence and identity of cooperatives in the growth and Credit Unions West Tulang Bawang. This research is a descriptive study. Population and sample in this research cooperative in the district of West Tulang Bawang and taken five cooperatives active for at least 5 years. Data collection method used is direct interview, library study, and documentation. The results of data analysis can be concluded that Based on Minister of Cooperatives and Small and Medium Enterprises of the Republic of Indonesia Number: 14 / Per / M.KUKM / XII / 2009 by judging from the 7 Aspects namely Aspect Capital, Assets Quality Aspects, Management Aspect, Aspect efficiency, Liquidity aspect, aspect and aspect Independence and Self Growth Cooperative. And the result Rating at Credit Unions in Tulang Bawang Barat has a quite healthy Predicate